Structural Mapping Inferred from Gravity Data to Image the Upper Lithospheric Structures and its Hydrocarbon Implication from Gwandu Formation NW, Nigeria - Adamu Abubakar; Othniel Kamfani Likkason; Ahmed Sadiq Maigari; Sani Ali (Indonesian Journal of Earth Sciences, 2022)
Presently a digitized composite satellite gravity data covering the Gwandu formation in Sokoto Basin were acquired and processed with a view to interpret the Bouguer anomalies as well to equally image the upper lithospheric structures beneath the Study area and its environs. The research work was aim to study the structural settings of crustal movement in the Gwandu formation. A least-square fitting polynomial surface of a third-degree order was applied in separating regional and residual gravity components from the Bouguer anomaly. The attributed low gravity sedimentary infill from the residual anomalies were tectonically trends NE -to- SW about the vicinities of Tambuwal, Goronyo, Gada and Argungu, Kolmalo and about Yauri, Koko and Jega, Kamba as well as Bagudo. Data enhancement techniques such as first vertical derivative, total horizontal derivative (THDR), analytic signal, spectral depth analysis, and the standard Euler deconvolution (SED) were applied to enhance deep-seated structures.  Results from the Spectral Analysis revealed that the average thickness of the sediments varies from 1.679 km to 4.181 km, outsized enough for hydrocarbon prospect.  The derivative maps revealed parallel to sub-parallel trending NW –to- SE, E -to- W fracture zones within the sedimentary infill underlying the study area, coinciding with the cretaceous zones.  Hence, the identified lineaments (faults or lithologic contacts) and structures in the area can be attributed to the tectonic setting of the area and probable migratory routes for hydrocarbon migration. More detailed ground gravity and seismic studies may lead to discoveries of structural or stratigraphic traps.